1983
DOI: 10.1002/bjs.1800701212
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac plexus block for pain in pancreatic cancer and chronic pancreatitis

Abstract: We have performed coeliac plexus block by standard percutaneous technique for disabling pain in 36 patients (13 with cancer and 23 with chronic pancreatitis). Eleven of the 13 cancer patients had complete pain relief initially and 7 remained pain free at the time of death. By contrast, only 12 of the 23 patients with pancreatitis had complete pain relief, 6 had partial relief and there was no effect in 5. The mean pain-free period in the chronic pancreatitis patients was only 2 months, and the longest 4 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
4

Year Published

1987
1987
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(68 citation statements)
references
References 3 publications
0
64
0
4
Order By: Relevance
“…Although widely used, there have been relatively few formally reported experiences with nerve blocks for long-term therapy of chronic pancreatitis. Leung et al [54] studied the use of celiac block in 23 patients with chronic pancreatitis. Twelve of the 23 had complete analgesia, whereas six had partial relief.…”
Section: Nerve Blockadementioning
confidence: 99%
“…Although widely used, there have been relatively few formally reported experiences with nerve blocks for long-term therapy of chronic pancreatitis. Leung et al [54] studied the use of celiac block in 23 patients with chronic pancreatitis. Twelve of the 23 had complete analgesia, whereas six had partial relief.…”
Section: Nerve Blockadementioning
confidence: 99%
“…Until recently, the least invasive method has been chemical coeliac ganglion block. This procedure has not been widely accepted, largely because of its unpredictable success and the brevity of response (Leung & Bowen-Wright, 1983). Peripancreatic denervation has been performed sporadically with good results (Hiraoka et al 1986).…”
Section: mentioning
confidence: 99%
“…This involves the injection of a neurolytic agent like alcohol into the region of the celiac plex us. The reported success of this technique for relieving the pain of chronic pancreatitis varies from an initial relief of 81 and 78% reported by Bell et al [19] and Leung et al [22], respectively, to only 50% reported by Filshie et al [21], Pain relief lasted only a mean of 2 months (range 1 week to 4 months) according to Leung et al, while Bell et al found 63% of their patients showing long-term improvement (> 6 months). As seen, the results of these reports are some what conflicting.…”
Section: Celiac Plexus Blockmentioning
confidence: 81%